Implementasi Ideologi Pendidikan Matematika pada Pendidikan Guru Penggerak - Sorta Corie Ivana Panjaitan; Izwita Dewi; Elmanani Simamora (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The important role of teachers in education underlies the Ministry of Education, Culture, Research and Technology to issue Program Guru Penggerak in the 5th episode of Merdeka Belajar. Mathematics as a subject taught to students from the most secondary level to higher education requires reliable and professional teachers or educators. Philosophy or Ideology of mathematics awakens teachers to become more professional. Teachers who understand the origin and methods of developing Educational Ideology, specifically mathematics education, will be able to prepare themselves to provide better learning in the classroom. Seeing how the implementation of the ideology of Mathematics Education in Program Guru Penggerak, more specifically on the educational materials and exercises received when participating in mobilizing teacher education, epistemologically and ethically further strengthens the views of every teacher, especially mathematics teachers, are expected to follow Program Guru Penggerak to become more professional in their fields. The ideology of Pancasila is in line with the ideology of Mathematics Education on Progressive Educator and Public Educator.